Mapping Political Discussions on Twitter: Where the Elites Remain Elites - Dagoula, Chrysi (2019)
This article compares digital arenas such as Twitter with the principles prescribed by the bourgeois public sphere, to examine how close or far these arenas are from Habermas’ original concept. By focusing on one of the criteria, the current influence of elites on political debate, it discusses the Habermasian principles of general accessibility and non-dominance of the elites as prerequisites for a functioning public sphere. This study finds that even though there are few access restrictions on Twitter and despite the fact that no one, in principle, is excluded from the platform, there is no apparent elimination of privileges and the elites maintain their elite status within its borders. Methodologically, the article relies on empirical research of hashtagged exchanges on Twitter during the General Elections in the United Kingdom in 2015. Through the mapping of Twitter as a synthesis of dialogic arenas, it explores the elite-focused discourse and the vocal actors in the stream, underscoring that the presence of the elites, even in an indirect way. Drawing on these elements, the article argues for a reconceptualization of the normative perception of the public sphere, suggesting the notion of exclusion is a complex issue that includes expanding notions of publics to also include those topics being discussed. Finally, it focuses on the significance of journalism in relation to political dialogue and argues that the move towards less elite-centered arenas largely depends on journalism.